KEMAMPUAN ANTIBAKTERI SENYAWA EKSTRAK KENCUR (KEAMPFERIA GALANGAL LINN) TERHADAP PERTUMBUHAN SALMONELLA TYPHI - Sri Nopita Primawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
Abstract: Keampferia galangal linn or known as kencur is a herb that is widely used by the community with various benefits such as influenza in infants, headaches, sprains, relieve fatigue, gastric inflammation, cough, expedite menstruation inflammation of the ears of children, dirty blood, sore eyes, diarrhea, colds. Therefore it is necessary to conduct scientific research to see the antibacterial ability of kencur extract (Keampferia galangal Linn) against Salmonella typhi growth. This study aims to determine the antibacterial ability of kencur extract compound on S. typhi growth. The type of this research is descriptive experiment, methanol kencur extract. This research uses consensus of different extract of methanol kencur that is 25%, 50% and 75% which will be tested on S. typhi to see the obstacle zone. Given cipro as a positive control and aquades as control negativenya. On the 3rd day all sampell observed the clear zone and written in the primary data. The obtained data is described to explain the ability of the extract zone of methanol kencur. It was found that the extract of methanol, cipro and aquades showed the bioactive compounds contained in kencur gave a low effectiveness against inhibition of S. thypi bacteria growth.